Preparation, Characterization and Catalytic Activity of Copper(II) Oxide Nanoparticles (Dhaka University Journal of Science, 2018)
An environmental benign synthetic route was used for preparation of copper(II) oxide nanoparticles from copper(II) sulphate precursor. Precipitates of copper(II) hydroxide were prepared from CuSO4.5H2O and NaOH. The product was then calcined at 350˚C to get the expected copper(II) oxide nanoparticles. Characterization of prepared sample was carried out by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), FTIR spectroscopy, X-ray powder diffractometry and reflectance measurement. SEM images show that the particle size was less than 100 nm. It is evident from the EDS analysis that the prepared sample was pure and contains only the atoms of Cu and O. XRD pattern confirmed the presence of only CuO in the sample. This result was supported by FTIR spectrum. The prepared CuO was used to study the adsorption and photodegradation of brilliant red (BR) in aqueous medium. The catalytic activity of CuO was investigated and compared with that of commercial CuO.Dhaka Univ. J. Sci. 66(1): 9-13, 2018 (January)